Endbearing pile: spun pile / Abdullah Zamzami Azaiz - Azaiz, Abdullah Zamzami (Universiti Teknologi MARA, Perak, 2015)
Piling is the essential support needed for any kind of structure. So focus of this report is explains about deep foundation and end-bearing pile: spun pile. All explanation about deep foundation and end-bearing pile: Spun piles based on case study construction project propose a new mosque at Mengabang Telipot village, Kuala Terengganu, Terengganu. This report was discussed what is deep foundation and what types of deep foundation. So, this report was explained end-bearing pile as one type of deep foundation. The objective of this report is to study about installation process of deep foundation and end-bearing piles: spun pile. It will focus on how spun pile was installed in the case study by using driven hammer technique. Other than that, this study can introduce the materials, plant and machineries involved during installation process of end-bearing pile: spun pile. After that, this study also discusses about the method used to test the installation of end-bearing pile: spun pile. To collect the information about end-bearing pile: spun pile, there are many study methods were used. The study method were used are interview, observation and reference books. The interview and observation method were conducted on case study, while reference books as theoretical study. So, this report was explaining detail about deep foundation and end-bearing pile: spun pile based on case study.